Using Fundamental Identities Objectives: Recognize and write the fundamental trigonometric identities Use the fundamental trigonometric identities to evaluate trigonometric functions, simplify trigonometric expressions, and rewrite trigonometric expressions
Fundamental Identities
Fundamental Trigonometric Identities Pythagorean Identities
Simplify an Expression Simplify cot x cos x + sin x. Click for answer.
Example: Simplify 1. Factor csc x out of the expression.
2. Use Pythagorean identities to simplify the expression in the parentheses.
3. Use Reciprocal identities to simplify the expression.
Simplifying a Trigonometric Expression
Factoring Trigonometric Expressions Factor the same way you would factor any quadratic. If it helps replace the “trig” word with x Factor the same way you would factor
Make it an easier problem. Let a = csc x 2a2 – 7a + 6 (2a – 3)(a – 2) Now substitute csc x for a.
Factoring Trigonometric Expressions
Adding Trigonometric Expressions (Common Denominator)
Fundamental Identities
Simplifying Trigonometric Expressions Claim: Proof:
4.2 Verifying Trigonometric Identities Verifying identities Testing identities using a graphing calculator
Verifying Identities Verify right-to-left:
Verifying Identities Using a Calculator Graph both sides of the equation in the same viewing window. If they produce different graphs they are not identities. If they appear the same the identity must still be verified. Example:
Basic Trigonometric Identities In this powerpoint, we will use trig identities to verify and prove equations
c) tan x sin x + cos x = sec x Proving an Identity Prove the following: a) sec x(1 + cos x) = 1 + sec x = sec x + sec x cos x = sec x + 1 1 + sec x L.S. = R.S. b) sec x = tan x csc x c) tan x sin x + cos x = sec x L.S. = R.S. L.S. = R.S. 5.4.8
= (sin2x - cos2x)(sin2x + cos2x) = (1 - cos2x - cos2x) = 1 - 2cos2x Proving an Identity d) sin4x - cos4x = 1 - 2cos2 x = (sin2x - cos2x)(sin2x + cos2x) = (1 - cos2x - cos2x) = 1 - 2cos2x 1 - 2cos2x L.S. = R.S. e) L.S. = R.S. 5.4.9
Proving an Identity f) L.S. = R.S. 5.4.10